2011
DOI: 10.1016/j.aquatox.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The anti-estrogenic activity of sediments from agriculturally intense watersheds: Assessment using in vivo and in vitro assays

Abstract: The goal of the current study was to determine whether sediments from agriculturally-intense watersheds can act as a potential source of anti-estrogenic endocrine-disrupting compounds. The specific objectives of the current study were to determine 1) whether female fathead minnows (Pimephales promelas) experience alterations in endocrine function when exposed to sediments collected from agriculturally-intense watersheds and 2) if these sediments display anti-estrogenic activity in an in vitro assay. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 31 publications
1
25
1
Order By: Relevance
“…For example, Sellin Jeffries et al . () collected sediment from a site in the Bow Creek (Nebraska) watershed but did not find detectable concentrations of testosterone or progesterone immediately following collection. However, when these sediments were immersed in surface water collected from the same field site, the sediments accumulated detectable concentrations of these steroid hormones after seven days, suggesting that steroids present in the overlying water had sorbed to sediments during the course of the seven‐day period.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, Sellin Jeffries et al . () collected sediment from a site in the Bow Creek (Nebraska) watershed but did not find detectable concentrations of testosterone or progesterone immediately following collection. However, when these sediments were immersed in surface water collected from the same field site, the sediments accumulated detectable concentrations of these steroid hormones after seven days, suggesting that steroids present in the overlying water had sorbed to sediments during the course of the seven‐day period.…”
Section: Introductionmentioning
confidence: 97%
“…Caged fish studies conducted in the Elkhorn River and Bow Creek watersheds have shown that female fish deployed in these watersheds experienced alterations in endocrine function, as indicated by reductions in the mRNA expression of estrogen‐responsive genes (Sellin et al ., ; Sellin Jeffries et al ., ) (Figure ). When females were exposed to sediments from these watersheds under laboratory conditions, they experienced reductions in mRNA expression similar to those observed among females deployed in the field; however, this effect was not observed when females were exposed to overlying surface waters (Sellin et al ., ; Sellin Jeffries et al ., ). This finding indicates that sediments from these two agriculturally intense watersheds are a source of biologically available BACs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…EDCs originate from a variety of sources, such as treated wastewater effluent and agricultural, ranch, or urban run-off [2], [3], and are widespread in the aquatic environment [1], [4]. Examples of hormonal disruptions in fishes produced by EDCs include altered secondary sexual characteristics, males producing egg proteins (vitellogenin, choriogenin), and reduced sperm quality [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have utilized the results from single-EDC laboratory exposures to produce predictive population models [10], [11], to assess multiple genomic and organismal level endpoints in response to known environmental mixtures [12], and to link EDC-perturbations in gonad or gene expression changes in fish with reduced reproductive performance or varying degrees of urbanization or agricultural activity [2], [13], [14]. However, to date no single study has attempted to link exposure to different environmental EDC mixtures, such as urban and ranch run-off, with responses at multiple tiers of the biological hierarchy, including population-level effects, within one study system.…”
Section: Introductionmentioning
confidence: 99%